A benefit to biodiversity assessment: An Indian survey demonstrates that Cheiriphotis geniculata is a misidentification of the valid species Photis geniculata Barnard, 1935 (Crustacea: Amphipoda) - Brutto, Sabrina Lo; Joseph, Philomina (Zootaxa, 2023)
The amphipod crustaceans are an essential taxonomic group in the marine biodiversity assessment and response to environmental pollution or climate change. They play an important role in benthic food webs due to their high biomass, abundance and highly variable modes of feeding. However, our knowledge of the amphipod fauna is somehow incomplete and literature shows shortcomings regarding misidentification or lack of identification to species-level. A case of misidentification is herein reported and solved. The present paper aims at allocating Cheiriphotis geniculata K.H. Barnard, 1916 to the correct taxon Photis. The observations herein presented demonstrate that Cheiriphotis geniculata does fit the genus Photis and its nomenclature should be revised in future checklists and updated in the World Amphipoda Database. Photis geniculata is characterized by a gnathopod 2 with three processes on the palm of propodus and a geniculated dactylus. The present paper recommends Cheiriphotis geniculata is considered a nomen nudum and changed to the valid name Photis geniculata Barnard, 1935.